2011
DOI: 10.1016/j.jcf.2010.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Twice vs three-times daily antibiotics in the treatment of pulmonary exacerbations of cystic fibrosis

Abstract: This study confirms that twice daily dosing of both tobramycin and ceftazidime is safe and effective and may be considered more convenient than current dosing schedules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 14 publications
0
13
0
2
Order By: Relevance
“…2) [40]. Adeboyeku et al [41] showed that twice daily dosing of tobramycin and ceftazidime was comparable to thrice daily dosing in 146 CF patients. Although a number of studies comparing treatment outcomes and side-effects of a once daily dosing regimen did not show benefit [42][43][44], the TOPIC trial [43] demonstrated equal efficacy between once and thrice daily tobramycin when administered with thrice daily ceftazidime and based on urinary marker analysis there was also less acute renal damage in children, but no difference was shown in adult patients.…”
Section: Dosing Intervalsmentioning
confidence: 99%
“…2) [40]. Adeboyeku et al [41] showed that twice daily dosing of tobramycin and ceftazidime was comparable to thrice daily dosing in 146 CF patients. Although a number of studies comparing treatment outcomes and side-effects of a once daily dosing regimen did not show benefit [42][43][44], the TOPIC trial [43] demonstrated equal efficacy between once and thrice daily tobramycin when administered with thrice daily ceftazidime and based on urinary marker analysis there was also less acute renal damage in children, but no difference was shown in adult patients.…”
Section: Dosing Intervalsmentioning
confidence: 99%
“…A recent study has found that twice daily treatments of tobramycin and ceftazidime are just as effective as thrice daily infusions, and this reduced treatment regimen can be safer and more convenient than a three times a day schedule. Studies have demonstrated that the bacterial response to antibiotic treatment is completed within 14 days (Adeboyeku, Jones et al 2011), although in some cases, patients respond better to shorter or longer treatments (VanDevanter, O'Riordan et al 2010;Plummer and Wildman 2011). Many more antibiotic treatment regimens are used in clinics and hospitals, and optimization of therapy for an individual exacerbation event often relies on symptoms and pulmonary function testing.…”
Section: Antibiotic Treatmentsmentioning
confidence: 99%
“…There is a dearth of high quality evidence to guide antibiotic therapy for pulmonary exacerbations of cystic fibrosis (CF) and so we read with interest the paper by Adeboyeku et al [1], which compares twice and three times daily regimens for ceftazidime and tobramycin. Unfortunately this paper contains important methodological flaws and describes the existing literature in a manner which is misleading.…”
Section: The Editor Journal Of Cystic Fibrosismentioning
confidence: 99%